1993
DOI: 10.1111/j.1365-2621.1993.tb09382.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Relationships Between Surimi Sol and Gel as Affected by Ingredients

Abstract: Rheological properties of surimi sol showed that consistency index (K) was surimi concentration-dependent, as it decreased with increased level of ingredients except for carrageenan which increased K value. The flow behavior index and textural properties appeared to be a function of type and level of ingredients. Unlike starch and synergistic carrageenan, egg albumin, oil and i-carrageenan did not show a composite reinforcing effect. K values measured by rotational cylindrical spindle viscometry more closely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Yoo and Lee (49) found that native and modified starches could be blended and added to fish protein gels at a maximum concentration of 4% to improve gel strength. Compressive force values increased from approximately 45-55 kg as starch concentration increased from 0 to 4%, which indicates a composite reinforcing effect of starch in the protein system.…”
Section: Starch and Surimi Seafoodmentioning
confidence: 99%
“…Yoo and Lee (49) found that native and modified starches could be blended and added to fish protein gels at a maximum concentration of 4% to improve gel strength. Compressive force values increased from approximately 45-55 kg as starch concentration increased from 0 to 4%, which indicates a composite reinforcing effect of starch in the protein system.…”
Section: Starch and Surimi Seafoodmentioning
confidence: 99%
“…These functional protein additives have been examined: whey (Burgarella and others 1985a, 1985b; Weerasinghe and others 1996; Liu and others 2000), caseinate (Camou and Sebranek 1990), egg albumen (Burgarella and others 1985a, 1985b; Hamann and others 1990; Pietrasik and Li‐Chan 2002), soy (Kurth and Rogers 1984; Feng and others 2003; Ramírez‐Suárez and Xiong 2003), wheat gluten (Ramírez‐Suárez and others 2005), cereal proteins (Chang‐Lee and others 1990; Chung and Lee 1990), and blood plasma and globin proteins (Autio and Mietsch 1990; Park 1994; Kang and Lanier 1999; Lou and others 2000). In addition, these nonprotein additives have been used in surimi and other meat products especially restructured meats; starch (Chen and others 1993; Yoo and Lee 1993; Yoon and others 1997a, 1997b; Kong and others 1999a, 1999b, 2001) and hydrocolloids such as carrageenan, alginate, pectins, xanthan gum, locust bean gum, and guar gum (Gómez‐Guillén and others 1997; Montero and others 2001; Pérez‐Mateos and others 2001; Barrera and others 2002; Ramírez and others 2002; Verbeken and others 2005). Regardless of the reason for including additives in meat products, gelation properties will be influenced.…”
Section: Additivesmentioning
confidence: 99%
“…Budig and Klima (1990) surveyed reasons for protein additives in meat products and compared vegetable and animal proteins. The textural and nutritional effects of protein additives such as soy protein isolate, whey protein concentrate, dried egg white, soy flour, and texturized soy protein on different forms of fish have been reported (Rockower et al, 1982;Iso et al, 1985;Chang-Lee et al, 1990;Yoo and Lee, 1993).…”
Section: Introduction the Gel-formingmentioning
confidence: 96%